Climate variability and agricultural productivity in MENA region - Imed Drine (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
The Middle East and North Africa (MENA) region is particularly vulnerable to climate change. The severity of climate-change impacts is related to the geographic and ecological particularity of the region. The majority of countries in the MENA region belong to the hydraulic poor regions located between the tempered region of the Northern hemisphere and the inter-tropical region, characterized by scarcity and spatial and temporal rainfall variability. This paper describes, first, the interaction between climate changes, agriculture and food security in the MENA region. Second, an empirical model is used to test the impact of climate variability on agricultural productivity. Our results suggest that lower precipitation, heat waves and drought are the main causes of decreasing agricultural productivity in the region.
Keywords: O1; Q1; Q54; Q56; 330; agricultural productivity; climate change; MENA region; Malmquist productivity; Klimawandel; Landwirtschaft; Malmquist-Produktivitätsindex; MENA-Staaten